Prevalence, diagnosis, and manifestations of brucellosis: A systematic review and meta-analysis - Khoshnood, Saeed; Pakzad, Reza; Koupaei, Maryam; Shirani, Maryam; Araghi, Almas; Irani, Golnaz Mokhtari; Moradi, Melika; Pakzad, Iraj; Sadeghifard, Nourkhoda; Heidary, Mohsen (Frontiers in Veterinary Science, 2022)
Objectives Brucellosis is one of the most prevalent zoonotic diseases common between humans and animals. Despite eradication efforts, the burden of the disease is well-known in endemic countries and in countries where brucellosis has not been an important health issue until recently. The aim of this study was to evaluate the prevalence, diagnosis, and manifestations of brucellosis. Methods In this study, PubMed, Web of Science, Scopus, Embase, and Google scholar databases were systematically searched to find studies published from 2011 to 2021. The search was conducted using text words and Medical Subject Headings (MeSH) Terms on the prevalence of brucellosis. Stata software 14.0 was used for all analyses. Results Based on the results, the pooled prevalence of brucellosis was 15.27% (95% CI: 9.68–21.86; heterogeneity I2 index: 97.43; p < 0.001) for man and 15.33% (95% CI: 7.19–25.75; heterogeneity I2 index: 98.19; p < 0.001) for woman. Age (coefficient: 0.240; p = 0.480), gender (coefficient: −0.017; p = 0.800), and publication year (coefficient: 0.114; p = 0.861) showed no significant effect on heterogeneity among studies. Egger's test indicated a significant publication bias for the prevalence of brucellosis (coefficient 3.894; p < 0.001). Moreover, the trim-and-fill method exhibited that the adjusted prevalence of brucellosis (18.30%, 95% CI: 14.10–22.52) was not significantly different from the original prevalence of brucellosis. Conclusion The pooled estimate for brucellosis prevalence was estimated as 15.53%. To better understand the epidemiology of brucellosis globally, more extensive studies are needed to be conducted throughout the world, especially in developing and low-income countries.